(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The essentials and basics of sustainable tourism are analyzed. New trends, problems and principles of sustainable tourism management are introduced. Environmental, social and economic problems caused by tourism is discussed. It is analyzed that sustainable tourism is not a type of tourism, it is ideological and methodological basis for any kind of tourism activity. The basic directions of sustainable tourism management are related to green-washing, tourism carrying capacity, regional development indicators, value chain, types of tourists, knowledge-based economy, management of cultural heritage, collaboration between university, industry and government.